The Nursing Practice Environment and Job Satisfaction, Intention to Leave, and Burnout Among Primary Healthcare Nurses: A Cross-Sectional Study - Pedro Lucas; Élvio Jesus; Sofia Almeida; Patrícia Costa; Paulo Cruchinho; Gisela Teixeira; Beatriz Araújo (Nursing Reports)
Background: The nursing practice environment significantly influences nurses’ job satisfaction, turnover, and burnout; therefore, it is essential to promote favorable environments to ensure the retention of qualified professionals. Improving the nursing practice environment is a low-cost organizational strategy associated with satisfaction, retaining professionals, and reducing burnout. The aim of this study was to assess the relationship between the nursing practice environment and job satisfaction, turnover, and burnout among primary healthcare nurses in Portugal. Methods: A descriptive, cross-sectional, and correlational study was carried out based on data from the RN4CAST Portugal Project. The Nurse Survey Instrument (Core Nurse Survey) of the RN4Cast Project (2018) was used for data collection. The sample consisted of 1059 nurses from fifty-five health center groups in mainland Portugal, fifteen health centers in the Autonomous Region of Madeira, and six health centers in the Autonomous Region of the Azores. Results: Primary healthcare nurses in Portugal rated the nursing practice environment as unfavorable or mixed, with an average (<semantics><mover accent="false">x¯</mover></semantics>) of 2.5 (standard deviation (SD) = 0.4), which is associated with lower job satisfaction, with an average of 2.0 (SD = 0.4), moderate intention to leave, with 40.3%, and low levels of burnout, with an average of 1.6 (SD = 0.8). There was also a negative correlation between the nursing practice environment and burnout (r = −0.28) and its dimensions. Emotional exhaustion (r = −0.35) represents the individual dimension of stress and physical exhaustion, corresponding to feelings regarding the depletion of emotional and physical resources, depersonalization (r = −0.18) represents the interpersonal context dimension of burnout, and a lack of personal accomplishment (r = −0.15) represents the self-assessment dimension of burnout and refers to feelings of incompetence and a lack of confidence and self-efficacy at work. Conclusions: The quality of the work environment is associated with greater job satisfaction and a reduction in burnout. For this reason, improving the work environment has therefore been associated with increased job satisfaction and reduced burnout among primary healthcare nurses, promoting nurse retention and the well-being of healthcare teams.